2003
DOI: 10.5479/si.00810282.618
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the genera and families of Zeiform fishes, with comments on their relationships with tetraodontiforms and caproids

Abstract: Tyler, James C, Bruce OToole, and Richard Winterbottom. Phylogeny of the Genera and Families of Zeiform Fishes, with Comments on Their Relationships with Tetraodontiforms and Caproids. Smithsonian Contributions to Zoology, number 618, 110 pages, 90 figures, 2 tables, 2003.-This cladistic study, using 103 putatively informative characters (mostly osteological) of representatives of all of the genera of zeiforms, a primitive tetraodontiform, both genera of caproids, and numerous outgroups, strongly supports th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
120
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(135 citation statements)
references
References 25 publications
11
120
3
1
Order By: Relevance
“…Tyler & Santini (2005) noted that all the earliest and most primitive forms of caproids, tetraodontiforms, and zeiforms are individuals of less than 6 cm SL, and all are much smaller than their extant relatives. Tyler et al (2003) and Tyler & Santini (2005) suggested that paedomorphic processes were important in the early evolution of all three groups. We suggest that a simpler hypothesis is that the last common ancestor of the zeomorphs was already a very small species.…”
Section: Caprosimilis Carpathicus Sp Nov Figures 3-9mentioning
confidence: 99%
See 4 more Smart Citations
“…Tyler & Santini (2005) noted that all the earliest and most primitive forms of caproids, tetraodontiforms, and zeiforms are individuals of less than 6 cm SL, and all are much smaller than their extant relatives. Tyler et al (2003) and Tyler & Santini (2005) suggested that paedomorphic processes were important in the early evolution of all three groups. We suggest that a simpler hypothesis is that the last common ancestor of the zeomorphs was already a very small species.…”
Section: Caprosimilis Carpathicus Sp Nov Figures 3-9mentioning
confidence: 99%
“…-In the description we indicate in sqare brackets [ ] the coding of morphological characters used in subsequent phylogenetic analysis. The numbers of the characters (Appendix 1) are in general the same as in Tyler et al (2003) and Tyler & Santini (2005).…”
Section: Caprosimilis Carpathicus Sp Nov Figures 3-9mentioning
confidence: 99%
See 3 more Smart Citations